Gender study on the relationships between science interest and future career perspectives. Issue 1 (2nd January 2019) - Kang, Jingoo; Hense, Jonathan; Scheersoi, Annette; Keinonen, Tuula
ABSTRACT: Gender disparities in STEM fields have been under extensive study, the focus of which has been on future career aspirations. However, the primary phases in gender differences are still ambiguous when examined from this perspective, possibly due to the fact that most of the studies have targeted samples of upper secondary school or college students. As such, in this study we examined the transient period to lower secondary school; our aim was to discover to what extent relationships between factors of students' science interest and career perspectives differ between male and female. Based on previous studies and analyses, we selected three future career perspective variables – outcome, personal time, and innovation orientations – and three defining features of interest – personal value, enjoyment, and cognitive aspect. The sample was conducted in Finland and comprised of 401 grade 7 students aged 13, using a multi-group structural equation modelling. This study found that during the transient period there were clear gender differences regarding interest and preferences of science subjects, as well as their relationship towards future career perspectives. To be specific, biology was preferred by females, and males preferred physics and chemistry. With regard to future career perspectives, female students' science interest was positively correlated with personal time- and innovation-oriented career perspectives; an outcome-oriented career expectation was negatively related to their interest. Interpretation and implication that might possibly arise from the results were also discussed.